2018
DOI: 10.1101/276675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost of resistance: an unreasonably expensive concept

Abstract: The cost of resistance, or the fitness effect of resistance mutation in absence of the drug, is a very widepsread concept in evolutionary genetics and beyond. It has represented an important addition to the simplistic view that resistance mutations should solely be considered as beneficial mutations. Yet, this concept also entails a series of serious difficulties in its definition, interpretation and current usage. In many cases, it may be simpler, clearer, and more insightful to study, measure and analyze the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…8 An absence of fitness cost may be due to favourable rearing conditions in the laboratory, failing to reveal costs that would be measurable under more stressful conditions. 7 Despite potential experimental limitations, our results are in line with Basit et al, who found no detrimental impact of the resistance to acetamiprid when comparing susceptible populations to an acetamiprid-selected population. 71 Likewise, in the MEAM1 species, resistance to pyriproxyfen was not associated with fitness cost.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…8 An absence of fitness cost may be due to favourable rearing conditions in the laboratory, failing to reveal costs that would be measurable under more stressful conditions. 7 Despite potential experimental limitations, our results are in line with Basit et al, who found no detrimental impact of the resistance to acetamiprid when comparing susceptible populations to an acetamiprid-selected population. 71 Likewise, in the MEAM1 species, resistance to pyriproxyfen was not associated with fitness cost.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that experiments on fitness cost measured in the laboratory cannot predict the effective fitness cost in the natural environment . An absence of fitness cost may be due to favourable rearing conditions in the laboratory, failing to reveal costs that would be measurable under more stressful conditions . Despite potential experimental limitations, our results are in line with Basit et al ., who found no detrimental impact of the resistance to acetamiprid when comparing susceptible populations to an acetamiprid‐selected population .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…"Cost of resistance" means that a resistance adaptation confers a fitness advantage under drug exposure, but it comes at a fitness cost in a treatment-free environment [2,15]. It is a phenomenon which has been widely studied in agricultural pests and antibiotic resistance [16,17] and is typically experimentally measured in one of three ways: i) Mono-culture experiments, which measure the growth rate of the resistant population in the absence of drug in isolation, ii) Competition experiments, which study the relative frequency of sensitive and resistant cells over time when cultured together, and iii) Reversal experiments, which explore how long it takes for resistant cells to lose their resistance mechanism if grown in the absence of drug ( Figure 1A-C).…”
Section: Introductionmentioning
confidence: 99%